Fame-Led to Sympathy: Content Analysis of Felicya Angelista’s Statement Related to the Israeli-Palestinian Conflict Using Roland Barthes Semiotic Approach - Husen Mony; Ivanaldy Kabul; Angkie Yudistia; Nurhajati Lestari (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
The video of Felicya Angelista discussing the Israeli-Palestinian conflict sparked controversy, with criticism directed at her for seemingly supporting Israel. The use of the word "war" without context and footage of Hamas attacking Israeli citizens contributed to this backlash, leading to calls to boycott Scarlett products. This research, utilizing Roland Barthes’ Semiotic Theory, aimed to analyze the denotation, connotation, and myths within the video's text, assessing its impact on Felicya's reputation and Scarlett products. Qualitative content analysis was conducted using data from Felicya's Instagram videos, netizen comments, and online news reports. The findings revealed denotatively that Felicya is crying and wiping her tears, Israeli civilians attacked by Hamas, and Felicya stood on humanity and peace. The denotational meanings were Felicya expressed sadness for the victims especially parents and children, and Felicya appearing neutral. However, connotatively, she was perceived to support Israel. Myths surrounding the expression of sadness, artists' involvement in the conflict, and the conflict's religious nature were also identified. The video faced criticism from netizens, leading to calls for boycotting Scarlett products due to Felicya's perceived alignment with Israel. In summary, while the video portrayed Felicya's neutrality denotatively, it connotatively suggested support for Israel, contributing to backlash and calls for boycotts.